2019
DOI: 10.1177/1545968319846120
|View full text |Cite
|
Sign up to set email alerts
|

Long-Dose Intensive Therapy Is Necessary for Strong, Clinically Significant, Upper Limb Functional Gains and Retained Gains in Severe/Moderate Chronic Stroke

Abstract: Background. Effective treatment methods are needed for moderate/severely impairment chronic stroke. Objective. The questions were the following: (1) Is there need for long-dose therapy or is there a mid-treatment plateau? (2) Are the observed gains from the prior-studied protocol retained after treatment? Methods. Single-blind, stratified/randomized design, with 3 applied technology treatment groups, combined with motor learning, for long-duration treatment (300 hours of treatment). Measures were Arm Motor Abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 70 publications
13
115
1
2
Order By: Relevance
“…Despite this, the findings of this survey indicate that the reported overall dose of therapy is relatively small when compared with what is known to be effective from animal models of stroke rehabilitation34 and so may not realise the potential for recovery. This argument is supported by findings from other studies; several large, well-conducted trials offering similar amounts of upper limb therapy to those reported in the current study found minimal benefit35 36 while trials that used higher doses reported meaningful and significant changes 37 38. In addition to research trials, large improvements in upper limb functioning have been reported in a NHS-funded clinical service (the Queen’s Square Upper Limb Programme) that delivers 90 hours of multidisciplinary upper limb rehabilitation over 3 weeks 33.…”
Section: Discussionsupporting
confidence: 87%
“…Despite this, the findings of this survey indicate that the reported overall dose of therapy is relatively small when compared with what is known to be effective from animal models of stroke rehabilitation34 and so may not realise the potential for recovery. This argument is supported by findings from other studies; several large, well-conducted trials offering similar amounts of upper limb therapy to those reported in the current study found minimal benefit35 36 while trials that used higher doses reported meaningful and significant changes 37 38. In addition to research trials, large improvements in upper limb functioning have been reported in a NHS-funded clinical service (the Queen’s Square Upper Limb Programme) that delivers 90 hours of multidisciplinary upper limb rehabilitation over 3 weeks 33.…”
Section: Discussionsupporting
confidence: 87%
“…The therapy intensity delivered in this study typically exceeded the amount of movement practice reported in the literature for conventional physio-or occupational therapy sessions (1.45 rep/min vs 0.92 rep/min) [60]. Still, compared to the knowledge gained from animal studies and to recent high-dose clinical studies [61][62][63], this intensity might not be sufficient. It is important to note, however, that one "repetition" using the neurocognitive approach is not directly comparable to, e.g., reaching movements as typically reported in the literature.…”
Section: Potential Of Neurocognitive Robot-assisted Rehabilitation Ofmentioning
confidence: 75%
“…The therapy intensity delivered in this study typically exceeded the amount of movement practice reported in the literature for conventional physio-or occupational therapy sessions (1.45 rep/min vs 0.92 rep/min) [58]. Still, compared to the knowledge gained from animal studies and to recent highdose clinical studies [59][60][61], this intensity might not be sufficient. It is important to note, however, that one "repetition" using the neurocognitive approach is not directly comparable to, e.g., reaching movements as typically reported in the literature.…”
Section: Potential Of Neurocognitive Robot-assisted Rehabilitation Ofmentioning
confidence: 76%